Getting a GRiPP on everyday schistosomiasis: experience from Zimbabwe. Issue 12 (12th October 2016) - MUTAPI, FRANCISCA
SUMMARY: Schistosomiasis, commonly known as bilharzia, is a parasitic disease prevalent in Africa, Asia and South America. The majority of the cases occur in Sub-Saharan Africa where schistosomiasis is a major public health problem impacting on child health and development as well as adult health when infections become chronic. Control of schistosomiasis is by treatment of infected people with the antihelminthic drug praziquantel. Current schistosome control programmes advocated by the World Health Assembly in 2001 are aimed at regular school-based integrated deworming strategies in order to reduce development of severe morbidity, promote school health and to improve cognitive potential of children. Several countries in Africa have now embarked on national scale deworming programmes treating millions of children exposed to schistosomiasis in endemic areas without prior diagnosis of infection through mass drug administration programmes. Implementing such control programmes requires a concerted effort between scientists, policy makers, health practitioners and several other stake holders and of course a receptive community. This paper considers the contributions to global schistosome control efforts made by research conducted in Zimbabwe and the historical context and developments leading to the national schistosomiasis control programme in Zimbabwe giving an example of Getting Research into Policy and Practice.